A State‐Space Approach to Australian Gross Domestic Product Measurement. (June 2015) - Rees, Daniel M.; Lancaster, David; Finlay, Richard
Abstract: We use state‐space methods to construct new estimates of Australian gross domestic product growth from the published national accounts estimates of expenditure, income and production. Across a range of specifications, our measures are substantially less volatile than headline domestic product. We conclude that much of the quarter‐to‐quarter volatility in Australian domestic product growth reflects measurement error, rather than true shifts in the level of economic activity .